Enzyklopädie der slowenischen Kulturgeschichte in Kärnten/Koroška, Band 2: J-PI Von den Anfängen bis 1942 - Sturm-Schnabl, Katja (2016)
The Encyclopaedia of Slovenian cultural history in Carinthia (Austria) is conceaved as a pluridisciplinary and intercultural reference work with over 160 authors, some 1000 entries and in total over 2100 conceptual entries covering areas such as history, legal history, sociology, linguistics, dialectology, literature, ethnology, art history, biographic studies, terminology. It provides a cross-linked understanding of the geographical area as well as of the cultural and societal processes in the region from an innovative perspective.